2021
DOI: 10.3390/plants10112469
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Growth, Yield, Seed Production and Phytochemical Properties of Satureja khuzistanica Jamzad by Foliar Application of Boron and Zinc

Abstract: Satureja khuzistanica Jamzad is a valuable and endemic medicinal plant. Boron and zinc are essential elements for the vegetative and reproductive growth of plants and have significant effects on yield, essential oil composition and the seed production of plants. To investigate the effects of the foliar application of zinc and boron on the growth, yield, seed production and phytochemical properties of S. khuzistanica, a study was conducted in a factorial experiment with three replicates in two consecutive years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
2
9
1
Order By: Relevance
“…In the current study, B application at 50 ppm significantly improved the seed quality traits, crude oil content, crude protein content and total antioxidant activity in both genotypes and seasons (Tables 2 and 3). In harmony with our results, Mumivand et al (2021) reported that foliar application of B had a significant effect on the essential oil content and yield of S. khuzistanica. Also, Hemantaranjan and Trivedi, (2015) and Mekki, (2016) recorded an increase in amino acids, protein and oil contents Egypt.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, B application at 50 ppm significantly improved the seed quality traits, crude oil content, crude protein content and total antioxidant activity in both genotypes and seasons (Tables 2 and 3). In harmony with our results, Mumivand et al (2021) reported that foliar application of B had a significant effect on the essential oil content and yield of S. khuzistanica. Also, Hemantaranjan and Trivedi, (2015) and Mekki, (2016) recorded an increase in amino acids, protein and oil contents Egypt.…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, the exogenous application of B increased the total seed yields of wheat, rice and maize by 14, 14 and 20%, respectively, (Ahmed et al, 2012). Also, the results of Mumivand et al, (2021) suggested that the foliar application of B can be considered a suitable method to increase the quantity and quality of the crop and seed yields of S. khuzistanica. In fact, the increase in seed yield of summer squash seeds by B application in the current study may be due to the increase in the seed yield component traits, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The higher accumulation of plant secondary metabolites in response to high PAR intensity could also be explained by the ecological functions of these compounds as a part of a plant defense mechanism against high light intensity(Raffo et al, 2020). Differently from what observed in this research, shading of solar radiation has been associated to the increased essential oil content of some species, due to the protection conferred by shading against the very intense radiation stress(Degani et al, 2016;Mousavinik et al, 2016).The essential oil yield of oil-bearing plants is thoroughly dependent on the plant biomass and percentage of essential oil(Mumivand et al, 2021b). The extent of increasing the essential oil content due to enriched UV-B irradiation was higher than that of decreasing the leaf dry weight.…”
contrasting
confidence: 58%
“…Zinc (Zn) has played a pivotal role in upregulating vital physiological and metabolic processes in enhancing seed germination, pollen grain formation, and fertilization and preserving the plant pigment system [22] and crop biomass production [23]. In addition, it functions as a cofactor in regulating enzymes such as oxidoreductases, transferases, hydrolases, isomerases, lyases, and ligases [24].…”
Section: Introductionmentioning
confidence: 99%